(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article explores an integrated digital platform approach to the development of rural territories in Ukraine, focusing on comprehensive management of engineering, land, and architectural resources at the community level. The relevance of the study is determined by the need to overcome fragmented decision-making, outdated spatial data, and limited institutional capacity of local communities, especially in the context of post-war recovery and sustainable rural development. The paper proposes a conceptual model of an integrated digital platform that combines engineering assessment and modelling (White Due Diligence Engineering), land and legal analysis (Triada Land & Legal), and urban and architectural planning tools (SigmaGeoPort Urban). The functional capabilities of the platform are analyzed, including risk identification, spatial scenario modelling, infrastructure planning, land-use optimisation, and preparation of investment-ready project packages. The study demonstrates the practical impact of digital platforms on improving transparency of asset management, reducing technical and legal risks, accelerating investment project preparation, and supporting evidence-based spatial planning. Particular attention is paid to the role of such platforms in empowering young professionals by providing access to real data, applied analytical tools, and interdisciplinary skills at the intersection of GIS, engineering, architecture, and territorial development. The findings confirm that integrated digital platforms represent a key instrument for sustainable rural development and the formation of resilient, investment-attractive communities in Ukraine.